Review of Acknowledgment Based Techniques for Detection of Black Hole/Gray Hole Attacks in MANETs (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2013)
In Mobile Ad hoc NETworks (MANETs) nodes communicate via wireless links, without any fixed infrastructure like base stations, central servers or mobile switching. Each node in MANET can act as a host or as a router. Due inherent characteristics like decentralization, self configuring, self -organizing networks, they can be deployed easily without need of expensive infrastructure andÂ  have wide range of military to civilian and commercial applications. But wireless medium, dynamically changing topology, limited battery and lack of centralized control in MANETs, make them vulnerable to various types of attacks. This paper focus on network layer packet dropping attacks â€“ Black Hole & Gray Hole attacks in Dynamic Source Routing (DSR) based MANETs and discuss various pros and cons of acknowledgement based techniques for detection of above said attacks.